2008
DOI: 10.1002/casp.996
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reactions, coping and long‐term consequences of perceived discrimination among the Mapuche people of Chile

Abstract: Although a substantial body of research has now documented the negative mental and physical health impacts of discrimination on various minority/non-dominant groups, little has been reported on the impacts of such discrimination on indigenous populations. In this study, we investigated the selfreported emotional reactions, coping responses and long-term impacts of discriminatory experiences among 50 Mapuche adults in Chile. The limited literature suggests that a substantial proportion of the Chilean majority s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 51 publications
(33 reference statements)
0
19
0
2
Order By: Relevance
“…The majority of A prevailing attitude within contemporary Chilean society is the presence of prejudice and discrimination against Mapuches that has been documented extensively in the literature. Prejudice and discrimination have been reported in everyday oral interaction among Chileans (Merino and Quilaqueo, 2003;Merino, Pilleux, Quilaqueo and Millamán 2004;Merino, 2006;Mellor, Merino, Saiz and Quilaqueo 2009;Merino and Mellor, 2009); in public and political discourse (Merino and Quilaqueo,2004;San Martín, 2001); and in educational practices and school textbooks (Rojas and Sepúlveda, 2002). In a longitudinal study Quilaqueo (2005-2007) …”
Section: Contextmentioning
confidence: 99%
“…The majority of A prevailing attitude within contemporary Chilean society is the presence of prejudice and discrimination against Mapuches that has been documented extensively in the literature. Prejudice and discrimination have been reported in everyday oral interaction among Chileans (Merino and Quilaqueo, 2003;Merino, Pilleux, Quilaqueo and Millamán 2004;Merino, 2006;Mellor, Merino, Saiz and Quilaqueo 2009;Merino and Mellor, 2009); in public and political discourse (Merino and Quilaqueo,2004;San Martín, 2001); and in educational practices and school textbooks (Rojas and Sepúlveda, 2002). In a longitudinal study Quilaqueo (2005-2007) …”
Section: Contextmentioning
confidence: 99%
“…Interestingly, Merino and Mellor (2009) revealed that among the four modes of discrimination, the verbal component was the most recurring and that school was the main context for discrimination, being the teacher the main perpetrator. However, these findings were based on interviews with adults who were reporting on their past experiences Mellor et al (2009) also investigated the impacts of these experiences, as reported by Mapuche people, which included feeling psychologically wounded, aroused anger, undifferentiated bad feelings, shame, and a sense of powerlessness.…”
Section: Introductionmentioning
confidence: 99%
“…What we do know is that discrimination is a consistent correlate of several negative outcomes. Experiences with discrimination are positively associated with anger (Mellor et al 2009), depressive symptoms, and alcohol abuse among Indigenous adults (Whitbeck, McMorris et al 2002; Whitbeck et al 2004). It is also associated with increased depressive symptoms, substance use, anger, suicide ideation, and problem behaviors among Indigenous adolescents (Walls et al 2007; Whitbeck et al 2001; Yoder et al 2006).…”
mentioning
confidence: 99%
“…Additionally, anger has been identified as a correlate of aggression or delinquency (Agnew 1992; Camodeca and Goosens 2005) and perceived discrimination (Mellor et al 2009; Whitbeck et al 2001). It is generally treated as a precursor to aggression (Camodeca and Goosens 2005) and hypothesized to be an intervening variable between strain (i.e., perceived discrimination) and delinquency (Agnew 1992).…”
mentioning
confidence: 99%